Device-based physical activity measures for population surveillance—issues of selection bias and reactivity - Christiansen, Lars Breum; Koch, Sofie; Bauman, Adrian; Toftager, Mette; Bjørk Petersen, Christina; Schipperijn, Jasper (Frontiers in Sports and Active Living, 2023)
Background Device-based measurement in physical activity surveillance is increasing, but research design choices could increase the risk of self-selection bias and reactive behaviour. The aim of this study is to compare the self-reported physical activity profiles of four different samples: participants in a large national survey, participants in a telephone-based survey of non-responders, participants in the large national survey who accepted the invitation to device-based measuring, and the same sample during the week of monitoring. Methods In October 2020, 163,133 Danish adults participated in a national survey and of those 39,480 signed up for device-based measurements. A balanced random sample (n = 3,750) was invited to wear an accelerometer of whom 1,525 accepted the invitation. Additionally, a short telephone-based survey on 829 non-responders to the national survey was conducted. Sociodemographic characteristics and self-reported weekly frequencies of physical activity across four domains are compared. Results The participants in the national survey were older, more often female, and more often not working. Participants in the telephone-based survey were younger, more often doing unskilled work, and were more often active at home and at work. The participants in the device-based sample were more often active during transport and leisure in the national survey, and participants categorized in the most active category increased during the week of monitoring from 29.0% to 60.7% and from 58.5% to 81.7% for active transport and leisure activities, respectively. Conclusion Recruiting a population representative sample for device-based measurement of physical activity is challenging, and there is a substantial risk of sample selection bias and measurement reactivity. Further research in this area is needed if device-based measures should be considered for population physical activity surveillance.